Spontaneous rotational Raman thermometry for air flow characterization in a turbomachine test rig. (31st July 2019) - Scherman, Michael; Santagata, Rosa; Faleni, Jean Pierre; Orain, Mikael; Bresson, Alexandre; Attal‐tretout, Brigitte; Krumme, Alexander; Polli, Dario; Marrocco, Michele; Zheltikov, Aleksei; Kiefer, Johannes
Abstract: Noninvasive and accurate measurements are essential to study the reactive flows in aeronautical engines. This paper reports the results of a unique measurement campaign providing the temperature flow field in a large‐scale facility turbomachine test rig using spontaneous rotational Raman scattering technique. Different planes of interest and operating conditions are probed, showing good agreement with thermocouple measurements. Fast temperature variations (>7.7 kHz) could be probed thanks to synchronization of the laser pulse with the rotor clock. The results outline the performance of in situ Raman technique to investigate steady and unsteady flows in turbine's conditions. Abstract : Temperature map obtained with Raman measurements in the turbomachine rig. This paper reports the results of a unique measurement campaign providing the temperature flow field in a large‐scale facility turbomachine test rig using spontaneous rotational Raman scattering technique. Different planes of interest and operating conditions are probed. Fast temperature variations (>7.7 kHz) are successfully measured thanks to synchronization of the laser pulse with the rotor clock. The results outline the performance of in situ Raman technique to investigate steady and unsteady flows in turbine's conditions.